Tropospheric ozone pollution, agriculture, and food security - Sarkar, A.; Datta, Sambit; Singh, P. (2016)
Increasing population and unsustainable exploitation of nature and natural resources have made "food security" a burning issue in the 21 st century. During the last 50 years, the global population has more than doubled, from 3 billion in 1959 to 6.7 billion in 2009. It is predicted that the human population will reach 8.7-11.3 billion by the year 2050. Growth in the global livestock industry has also been continuous over the last two decades. An almost 82% increase in future livestock is expected in developing countries within 2020, due to an expanding requirement for food of animal origin. Hence, the future demand of this increased human and livestock population will put enormous pressure on the agricultural sectors for providing sufficient food and fodder as well as income, employment and other essential ecosystem services. Therefore, a normal approach for any nation / region is to strengthen its agricultural production for meeting future demands and provide food security. Tropospheric ozone (O 3 ), a secondary air pollutant and a major greenhouse gas, has already been recognized as a major component of predicted global climate change. Numerous studies have confirmed the negative impact of O 3 on agricultural productivity throughout the world. The present chapter reviews the available literature, and catalogue the impact of this important gas pollutant on modern day agricultural production worldwide.